Enhancing the Thermal and Mechanical Performance of Asphalt Mixture Using SUPERPLAST T23 Polymer: An Applied Study on the Nalut–Wazen Road in Libya (Journal of Technology Research, 2025)
Plastic waste is widely distributed across the globe because of the developing enlargement of plastic industries, resulting in big portions of residual substances and posing severe environmental, financial, and health demanding situations. Recycling these wastes and reusing them as components in engineering applications—mainly in bendy pavement projects—represents a promising solution for waste mitigation, in particular when such reuse definitely complements the properties of asphalt combos. This look at objectives to assess the impact of the industrial polymer SUPERPLAST T23 on the thermal and mechanical overall performance of asphalt combos used inside the Nalut–Wazen avenue assignment in Libya. Bitumen of grade (60/70) become modified by incorporating varying polymer contents (zero%, 2%, four%, and 6%). Standardized exams have been performed, including the Marshall stability take a look at, oblique tensile power (ITS), wheel tracking test, and bending beam rheometer (BBR), in conjunction with microstructural analyses using Scanning Electron Microscopy (SEM) and Fourier Transform Infrared Spectroscopy (FTIR),The outcomes indicated that a 4% polymer content material represents the most desirable dosage, main to a forty% boom in Marshall stability, a 35% reduction in rutting intensity, and a 50% improvement in fatigue lifestyles. Additionally, the softening point accelerated while the penetration fee reduced, reflecting more desirable performance at excessive temperatures and stepped forward crack resistance at low temperatures. The look at recommends adopting this dosage to attain a overall performance grade of PG 76-10, suitable for the cruel climatic conditions of the location.
Keywords: SUPERPLAST T23; polymer-modified asphalt; thermal overall performance; rutting resistance; Nalut road